Intervensi Terapi Dukungan Psikologis pada Korban Terdampak Bencana yang Mengalami PTSD (Literature Review) - Indra Maulana; Sandra Febrianti; Bambang Aditya Nugraha (Universitas Malahayati Lampung, 2023)
ABSTRACT Trauma after a natural disaster is experienced by more than two-thirds of the population in their lifetime resulting in various mental and physical health consequences. As a result of disasters that often occur, people experience prolonged trauma, of the trauma factors caused include depression, anxiety, fear, dizziness, and nausea. PTSD disorders are the most common post-disaster psychiatric morbidity. Various psychological support interventions in patients with signs and symptoms of PTSD due to natural disasters have been developed and used by nurses. The purpose of this literature review is to describe the various therapeutic methods and interventions that have been applied so far as a post-disaster recovery effort to develop nurses' competence in providing post-disaster psychological treatment. The method used is a literature review by searching for articles on three databases, namely Pubmed, ScienceDirect, and EBSCOhost. The study discussed psychological support therapy interventions for disaster victims who experienced PTSD with a randomized control trial (RCT) and quasi-experimental study design in English with full text and published from 2017 to 2022. It found that there are 4 types of psychological support therapy interventions in disaster victims experiencing PTSD are Cognitive-Behavioural Therapy (CBT), Acceptance and Commitment Therapy (ACT), The Mental Health Integrated Disaster Preparedness Intervention, and Eye Movement Desensitization and Reprocessing (EMDR) Intervention. Behavioral therapy is one of the most frequently used options today. The principle of this theory is changes in daily behavior through a continuous learning process which will then affect the mindset and ultimately reduce levels of anxiety, stress, and depression. In addition to therapy that needs to be given, psychological support is also important to encourage patient motivation which then has an impact on accelerating the healing process. Keywords: PTSD, Disaster, Psychological Intervention ABSTRAK Trauma setelah bencana alam dialami oleh lebih dari dua pertiga populasi dalam hidup mereka yang mengakibatkan berbagai konsekuensi kesehatan mental dan fisik. Akibat bencana yang sering terjadi, masyarakat mengalami trauma berkepanjangan, beberapa faktor trauma yang ditimbulkan antara lain depresi, kecemasan, ketakutan, pusing, mual. Gangguan PTSD telah ditemukan sebagai morbiditas psikiatri yang paling umum setelah bencana. Beragam intervensi dukungan psikologis pada pasien dengan tanda dan gejala PTSD akibat bencana alam telah berkembang dan digunakan oleh perawat. Tujuan tinjauan pustaka ini adalah untuk menggambarkan ragam metode terapi dan intervensi yang telah diterapkan selama ini sebagai upaya pemulihan pasca bencana untuk mengembangkan kompetensi perawat dalam memberikan penanganan psikologis pasca terjadi bencana. Metode yang digunakan adalah literature review dengan pencarian artikel pada tiga basis data yaitu Pubmed, Sciencedirect, dan EBSCOhost. Studi yang ditinjau membahas terkait intervensi terapi dukungan psikologi pada korban bencana yang mengalami PTSD dengan desain penelitian randomized control trial (RCT) dan quasi experiment berbahasa Inggris dengan teks lengkap, serta dipublikasikan dari tahun 2017 – 2022. Ditemukan terdapat 4 jenis intervensi terapi dukungan psikologi pada korban bencana yang mengalami PTSD yaitu Cognitive-Behavioural Therapy (CBT), Acceptance and Commitment Therapy (ACT), The Mental Health Integrated Disaster Preparedness Intervention dan Intervensi Eye Movement Desensitization and Reprocessing (EMDR).Terapi perilaku (behavioral therapy) menjadi salah satu pilihan yang paling sering digunakan saat ini. Prinsip dari teori ini adalah perubahan perilaku sehari-hari melalui proses belajar yang terus menerus yang kemudian akan mempengaruhi pola pikir dan pada akhirnya menurunkan tingkat kecemasan, stress, dan depresi. Selain terapi yang perlu diberikan, dukungan psikologis juga penting untuk mendorong motivasi pasien yang kemudian berdampak pada percepatan proses penyembuhan. Kata Kunci: PTSD, Bencana, Intervensi Psikologis